Industrial development and economic policy / edited by Mohanty B. - B. Mohanty (ed.) (New Delhi, 1996)
The economic development in India since its Independence has been as fascinating at the diversity, variety and complexity of the land and the peoples of the country. Ever since the advent of planning in 1951 the country's planners and policy makers have attempted to reconcile the principles and practices of democratic welfare state with the Imperatives of development in the framework of a mixed economy. The foundations of economic development were laid by the dynamic first Prime Minister of Free India. Shri jawaharlal Nehru when he had the deep foresight to construct dams, steel plants and heavy engineering and capital goods industries. Progress has been both steady and erratic substantial and mearge and turns.
Keywords: Industries-India